Organizational Commitment's Role in Reducing Social Loafing in IMM Members: Peran Komitmen Organisasi dalam Mengurangi Social Loafing pada Anggota IMM - Apriat, Rika Ari Pamungkas Sah; Hardiansyah, Eko (Journal of Islamic and Muhammadiyah Studies, 2025)
The issue of social loafing can significantly reduce productivity within student organizations, including the Muhammadiyah Student Association (IMM) at Muhammadiyah University Sidoarjo. This study examines the relationship between organizational commitment and social loafing among IMM members, addressing a knowledge gap in understanding the extent of this relationship within Islamic student organizations. Using a quantitative correlational approach, the study surveyed 162 out of 400 IMM members, utilizing non-probability accidental sampling based on Isaac and Michael's table with a 10% error rate. The hypothesis posited a negative relationship between organizational commitment and social loafing. Data analysis was conducted using Spearman rank correlation with SPSS 20.0. Findings indicate a negative correlation (r = -0.107, p = 0.001), suggesting that higher organizational commitment is associated with lower social loafing among IMM members, with organizational commitment accounting for 7.4% of the variation in social loafing. This study’s novelty lies in its focus on the interplay between commitment and social behavior within a specific Islamic student organization. The implications of these findings underscore the importance of fostering strong organizational commitment to minimize social loafing and enhance group productivity. Further research could explore additional factors influencing social loafing in similar contexts. Highlights: Higher organizational commitment correlates with reduced social loafing among IMM members. Organizational commitment accounts for 7.4% of the variation in social loafing. Study fills a knowledge gap within Islamic student organizations' behavioral dynamics. Keywords: Organizational Commitment, Social Loafing, Student Organization, Muhammadiyah, Quantitative Study